Financial Derivatives and Risk Management: Retail Investors' View - Ramanjaneyalu, N.; Hosmani, A. P. (Indian Journal of Finance, 2010)
With the opening up of the economy to multinationals, the adaptation of liberalised economic policies, the economy is driven more towards the free market economy. It exposes the investors to various risks such as exchange risk, market risk, interest rate risk, economic risk and political risk and so on. With the integration of the financial markets and free mobility of the capital, risks also multiplied. In the present state of the economy, there is an urgent need for the investors to protect their interests by shifting some of the uncontrollable financial risks to those who are also to bear and manage them. Thus, risk management becomes a must for survival since there is a high volatility in the present financial markets. In this context, derivatives occupy an important place as a risk reducing mechanism. Derivatives are useful for reducing many of the risks mentioned above. History of financial markets has evidence to suggest that when risk management avenues are provided by means of derivatives, markets attract higher volumes of investments from savers, strengthening the markets in the process.